Graves’ disease presenting as unilateral anterior ischaemic optic neuropathy - Monigari, Naresh (BMJ Publishing Group, 2014)
We report a case of a 28-year-old man who presented with 1-day history of sudden diminution of vision in the right eye. Examination showed unilateral exophthalmos with restricted eyeball movement on upward gaze in the right eye. MRI of the orbit showed no evidence of compression of the optic nerve on the right side. Visual-evoked potential showed prolonged P100 in the right eye. Fundus examination revealed swollen optic disc and para papillary nerve fibre layer splinter haemorrhages with corresponding altitudinal field defect on perimetry suggestive of anterior ischaemic optic neuropathy.